ENGLISH ... WHERE DO WE GO FROM HERE? - Picard, J.H. (Scientia Militaria - South African Journal of Military Studies, 2012)
English and Other Languages Jespersen (1948) ascribes the tremendous variety of the English language to the freedom a writer was given in England to "... take his words where he chooses, whether from the ordinary stock of everyday words, from native dialects, from old authors, or from other languages, dead or living. The consequence has been that English dictionaries comprise a larger number of words than those of any other nation, and that they present a variegated picture of terms from the four quarters of the globe." (Jespersen, 1948: 15). The foreign words and phrases so abundantly present in English have immeasurably enriched the language. English not only easily incorporates foreign words but also assimilates syntactical elements from other languages. This feature of English is the very reason for its rapid evolvement into a world language. The English literatures of Canada, Australia, South Africa, the United States of America, New Zealand and other English-speaking countries have all succeeded in describing situations, backgrounds and personalities typical for their territories and often better than any other language could have done. In fact, English has become so integrated in certain countries that one describes the particular local brand of English as "South African English usage", "Australian English", "American English", etc. In South Africa, for example, it would be quite normal to find words from Afrikaans incorporated in an English text, the reader turning a blind eye to these: "If you’ll wear your nagmaal jacket next time ... I’ll be glad to show you all over my farm where I’m not going to plant potatoes ... That is, among the haak-en-steek thorns." (Bosman, 1971).